Stories from the forest - Johansson, Kornelia (2020)
In recent years, the concept of bioeconomy has evolved as an alternative to the fossil-based economy of today, providing a vision of an economy based on renewable resources. In Sweden, the concept has been adopted by dominant stakeholders in the forest industry, where the forest is identified as an important renewable resource and a mean to mitigate carbon dioxide. The aim of this study is to examine the discourse upheld by the major Forest Owners Associations in Sweden and to explore the perspectives of private forest owners. By using Hajer’s argumentative approach, text material from the websites of the FOAs is analyzed together with interviews with eight forest owners. The study finds that the FOAs represents a perspective on the bioeconomy where productive forestry and climate mitigation is in focus while social and environmental aspects are largely neglected. The forest owners are shown to put more emphasis on social and environmental sustainability in their forestry, hence partly rejecting the discourse that the FOAs upholds.